The imprint of Alan Swallow : quality publishing in the West - Nelson, W. Dale (UPCC book collections on Project MUSE., 2010)
Born and raised on the windswept prairies of northwest Wyoming, Alan Swallow (1915-1966) developed a passion for literature and poetry at an early age. Quickly realizing he was not suited to a life of farming and ranching, Swallo entered the University of Wyoming to study literature and earned a fellowship to further his studies at Louisiana State University. It was there, under the influence of Robert Penn Warren and Cleanth Brooks, that Swallow began his almost four-decade-long career as a publisher, teacher, and poet.